Pengaruh Intervensi Sistem Informasi Akuntansi terhadap Faktor yang Mempengaruhi Kinerja Karyawan. - Rio Johan Putra; Dewi Rochimah (Politeknik Ganesha Medan, 2022)
The purpose of this study is to examine the extent to which accounting information systems can intervene in internal control, organizational culture and business digitalization can affect employee performance. This research method is quantitative with questionnaire primary data distributed to 200 respondents of Jabodetabek finance & accounting employees. This study uses a Likert measurement scale and Structural Equation Modeling (SEM) data analysis techniques with smartPLS. The results of the study show that internal control has an effect on accounting information systems, organizational culture has an effect on accounting information systems, business digitization has an effect on accounting information systems, internal control has no effect on employee performance, organizational culture has no effect on employee performance, business digitization affects employee performance , the accounting information system has an effect to employee performance, the intervention of the accounting information system has a significant effect too on internal control on employee performance, the intervention of the accounting information system provides a significant influence on organizational culture on employee performance, the intervention of the accounting information system provides a significant effect of business digitization on employee performance . The implication of this research is that companies can use this research as a reference or as a recommendation if they want to develop better employee performance. This study has proven that in increasing employee performance there are many factors that need attention. In this study, information systems play an important role in improving employee performance because information systems are able to intervene in factors that affect employee performance.